Restoration of miR-127-3p and miR-376a-3p counteracts the neoplastic phenotype of giant cell tumor of bone derived stromal cells by targeting COA1, GLE1 and PDIA6. Issue 1 (1st February 2016) - Fellenberg, Jörg; Sähr, Heiner; Kunz, Pierre; Zhao, Zhefu; Liu, Li; Tichy, Diana; Herr, Ingrid
Highlights: A specific microRNA signature is silenced in giant cell tumors of bone. The neoplastic phenotype was analyzed after restoration of microRNA expression. Re-expression of miR-127 and miR-376a significantly inhibits neoplastic features. Novel target genes of miR-127 and miR-376a were identified. MiR-127, miR-376a and their target genes are promising new therapeutic targets. Abstract: Although generally benign, giant cell tumors of bone (GCTB) display an aggressive behavior associated with significant bone destruction and lung metastasis in rare cases. This and the very high recurrence rate observed after surgical resection ranging from 20 to 55% necessitates the development of more effective treatment strategies. To identify valuable therapeutic targets, we screened a previously identified microRNA signature consisting of 23 microRNAs predominantly down-regulated in GCTB. We preselected eight candidate microRNAs and analyzed the impact of their restored expression on the neoplastic phenotype of GCTB stromal cells (GCTSC). A consistent and significant inhibition of cell proliferation, migration, colony formation and spheroid formation could be induced by transfection of primary GCTSC cell lines with miR-127-3p and miR-376a-3p, respectively. Genome wide expression analysis of miR-127-3p and miR-376a-3p transfected cells revealed four novel target genes for each microRNA. Luciferase reporter assays demonstrated direct interactions of miR-127-3p with COA1 and direct interaction of miR-376a-3p with GLE1 and PDIA6, suggesting a pivotal role of these genes in the molecular etiology of GTCB. Interestingly, both microRNAs are located within a chromosomal region frequently silenced in GCTB and many other types of cancers, indicating that these microRNAs and their target genes are valuable therapeutic targets for the treatment of GCTB and possibly other tumor entities.